BURDICK, John. Blessed Anastácia: Women, Race, and Popular Christianity in Brazil. - Nunes, Maria José Rosado (Revista Estudos Feministas, 2003)
BURDICK, John. Blessed Anastácia: Women, Race, and Popular Christianity in Brazil.